A Review Multiphysics Modeling Techniques for PMSM-Based Electric Vehicle Drives - Md. Abu Saleh; Md. Mehedi Hasan Mia; Md. Jasim Uddin; Md. Sumon Ali (Control Systems and Optimization Letters, 2026)
The objective of this paper is to review Multiphysics modeling techniques for PMSM-based electric vehicle (EV) drives. Because of its great efficiency, power density, and ability to precisely adjust power, permanent magnet synchronous motors (PMSMs) have emerged as the go-to option for electric vehicle (EV) drives. However, a Multiphysics approach that incorporates mechanical, thermal, electromagnetic, and control system dynamics is necessary to effectively describe PMSM-based EV drives. This paper examines the benefits, drawbacks, and uses of several Multiphysics modelling approaches applied to PMSM-based EV drives. Analytical methods and finite element analysis (FEA) are two examples of electromagnetic modelling techniques that are examined in connection with loss prediction and motor design optimization. While mechanical modelling techniques concentrate on vibration and acoustic noise difficulties, thermal modelling procedures are examined to address heat dissipation and performance reliability. One of the main issues lies in the accurate representation of coupled losses electromagnetic, thermal, and mechanical especially under dynamic operating conditions typical of EVs. To improve the dynamic performance and fault tolerance of PMSM drives, control-oriented modelling techniques are also examined. Co-simulation frameworks that combine these several physical domains are also presented in the review, offering a thorough understanding of practical EV applications. The paper concludes by discussing future research possibilities in Multiphysics modelling for PMSM-based EV drives, with a focus on real-time simulation capabilities, computational efficiency, and artificial intelligence integration.